The Influence of Pet Can Packaging and Perceived Shelf-Life Information of Preservative-Free Products on Domestic Consumers’ Purchase Intention At Rujak Ambu, A Women-Empowerment-Based Export-Oriented MSME - Siti Jamilah; Ani Wahyu Rachmawati (Takaza Innovatix Labs Ltd., 2026)
This study aims to determine the effect of PET Can packaging and the perceived shelf-life information of preservative-free products on domestic consumers' purchase intention for Rujak Ambu instant seasoning. Rujak Ambu, a women-empowerment-based MSME, faces challenges in expanding its domestic market due to an overstock of export packaging (PET Cans). This research employs a quantitative method with a survey approach. Primary data were collected through questionnaires distributed to 97 respondents comprising current and potential consumers of Rujak Ambu. Data analysis included classical assumption tests, and multiple linear regression analysis using IBM SPSS Statistics. The results showed that: (1) Partially, the physical innovation of PET Can packaging does not have a significant effect on domestic consumers' purchase intention (Sig. 0.232). (2) Partially, the perceived shelf-life information of preservative-free products has a positive and highly significant effect on consumers' purchase intention (Sig. 0.000). (3) Simultaneously, PET Can packaging and the perceived shelf-life information of preservative-free products significantly influence purchase intention with a contribution (R Square) of 65.9%. These findings conclude that for traditional food products like rujak seasoning, premium packaging innovation must be integrated with educational label communication regarding shelf-life transparency and product safety to optimally boost purchasing decisions.